Ecological determinants of livestock depredation by the snow leopard Panthera uncia in Bhutan. (9th April 2021) - Lham, D.; Cozzi, G.; Sommer, S.; Wangchuk, S.; Lham, K.; Ozgul, A.
Abstract: Retaliatory killing due to livestock depredation is a major threat to snow leopard ( Panthera uncia ) conservation. To devise management actions that reduce livestock losses and the consequent retaliatory killing, we need to understand the factors that influence the snow leopard's diet and depredation on livestock. Here, we studied snow leopard diet and ecological determinants of livestock depredation in Bhutan by semi‐systematically collecting scat samples and analysing prey hair structure using a micro‐histological method. We identified five prey species. Most of the snow leopard diet consisted of wild ungulates (85.8%), mostly bharal (60.8%). Yak (14.2%) was the only livestock species in the scats. Livestock depredation was higher during summer and differed markedly among four protected areas characterized by various wildlife densities and human activities. These findings will help develop a site‐based management plan to ensure the long‐term persistence of the snow leopard in Bhutan. Abstract : We studied snow leopard diet and ecological determinants of livestock depredation in Bhutan. Snow leopard diet consisted of wild ungulates, mostly bharal and yak was the only livestock. Livestock depredation was higher during summer and differed markedly among four protected areas characterized by various wildlife densities and human activities.